Producción de audios educomunicativos para reforzar el proceso de aprendizaje y estimular la identificación de los contextos y la narrativa literaria a través de los sonidos en la materia de lenguaje de los 8vos años EGB de la Unidad Educativa Particular Francisca de las Llagas - Fonseca Moscoso, Augusto Javier (2016)
The following is a reflection on the significant changes in the educational and communicative process that is influenced by information and communication technologies (ICT). Taking into account the interactive learning in education and communication, the sense of relating the educator to the educator and the educational products, introduces us in an attractive way to teach and learn. One of the main requirements in teaching, regarding its pedagogical tools, requires the knowledge and design of digital products. The hurried technological revolution of the 21st century has given the opportunity to develop and apply educational knowledge as the design and production of content, thus transforming teaching into the current system of education. Computers, the Internet and the daily use of ICTs have given rise to a new educational environment capable of producing and creating a communicative scenario through ways of digitally representing reality, narrating realities and social relations, art and knowledge. The interpretation of the ICT revolution in education faces challenges in the new ways of narrating and giving meaning to learning, the way of teaching and learning takes another approach that makes it attractive and interesting to this process of education, how to develop Within the classroom and learning are inspired by the innovations that technological and digital development offers us.